From eco-innovation to sustainability: the role of public policy - Oliveira, Rúben João Batista (2021)
Purpose: This study aims to set empirical evidence on EI determinants to help trace more effective public policies in the field. Design/methodology/approach: Using the Portuguese CIS 14, with 7083 observations, nine logit models were estimated, evaluating probabilities of EI adoptions in general and on the role of their objectives and different policy approaches. Findings/highlights: Statistical support was found based nine hypotheses estimated. The findings confirm the positive effect of innovation in general, R&D, access to funds and size on the probability to eco-innovate. Otherwise, results shed light to the negative effect of higher technological regimes, open innovation and skill intensity on the same probability. Finally, results indicate a higher impact of non-technological innovations over technological innovations on the probability to EI. Research Limitations/implications: The CIS database is not purposefully made to evaluate EIs, lacking some details on its study. Also, the use of one single wave of CIS only allows for cross sectional data estimations, instead of a panel data. Additionally, it only covers one specific country, which may feel short for some generalizable results. Empirical implications: No single policy will meet all dimensions requiring a policy package, combining the demand and the supply side with both carrots and sticks. Originality/value: In this research, a straightforward methodology of analysis was performed producing valuable policy recommendations. Future analysis similarly performed in other CIS countries will allow international comparisons